Las personas con discapacidad privadas de libertad y sus Derechos Constitucionales. - Fernández Naula, Antonella Carolina (2023)
The purpose of this research was to determine whether the constitutional rights of persons deprived of liberty with disabilities are safeguarded in rehabilitation centers. It was a qualitative research with a descriptive and non-experimental approach. A survey was used as a data collection instrument directed to six judges of penitentiary guarantees, two prosecutors, and two free practice lawyers. The results showed that in rehabilitation centers the constitutional rights of persons deprived of liberty with disabilities are partially safeguarded due to the fact that Ecuadorian legislation has been effective in some cases, being one of the main problems of the penitentiary system, the overcrowding that leads to a deterioration of the living conditions and human dignity of the persons deprived of liberty. It was concluded that the constitutional rights of persons deprived of liberty with disabilities in prisons are based on respect for this vulnerable group. This research emphasizes that the Ecuadorian State is obliged to develop and implement a comprehensive penal policy based on the guarantee of human rights, ensuring the prevention of social violence, the adequate and not excessive use of pretrial detention and the execution of sentences in accordance with the constitutional principles of rehabilitation and social reintegration of persons deprived of liberty with disabilities.